Metropolitan Naga: A Continuing Challenge of Local Autonomy and Sustainability - Ruben G. Mercado; Victor B. Ubaldo (Philippine Institute for Development Studies (PIDS), 1998)
Under EO 102, the Metro Naga Development Council (MNDC) has been tasked to formulate, coordinate and monitor programs, projects and activities for the acceleration of economic development and social growth. This paper identifies the three major challenges that the MNDC has faced: first is the organizational machinery, financial sustainability and management of leadership transition and sustaining partnership.
Keywords: 330; governance; development program